Semiotic Analysis of Kembang Gadung Song in Kuda Renggong Cupu Muda Art of Rancaekek Group - Annisa, Auliya Ayu; Rita Milyartini (Jurnal Penelitian Musik, 2025)
This study aims to determine the musical and semiotic analysis of the Kembang Gadung song. This study uses a descriptive analysis method with a qualitative approach. In the data processing process, the researcher systematically compiles the data obtained from the literature review and analysis. Based on the data from the literature review results, the researcher will analyze the Kembang Gadung song sung by the singer in the Cuta Muda Rancaekek group. The findings of this study are that the Kembang Gadung song has the structure AAA'A' A''A'' A. This study concludes that the lyrics of the Kembang Gadung song as the opening of the Kuda Renggong performance have denotative and connotative meanings that refer to the values ​​of faith and local wisdom values ​​that are reinforced by the melody of the Kembang Gadung song itself.